UJI EFEKTIVITAS EMULGEL ANTI JERAWAT EKSTRAK ETANOL DAUN JERUJU (Acanthus ilicifolius) TERHADAP Staphylococcus aureus - rusli, Nirwati; Muh Azdar Setiawan; Yulianti Fauziah; Eny Nurhikmah; Esti Badia; Bonni Rubak; Riswanti Ruslan; Reymon; Isna Dwi Wulandari (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2025)
ABSTRACT The Jeruju plant is one of the true mangrove species that typically grows in coastal areas, rivers, swamps, and brackish water regions, and is used for medicinal purposes. Scientific data on Jeruju leaf (Achantus ilicifolious) extract indicate the presence of alkaloids, flavonoids, tannins, steroids, and saponins, all of which can be utilized for their antibacterial properties, particularly against the acne-causing bacterium Staphylococcus aureus. Staphylococcus aureus is known to cause skin blockages, which in turn trigger inflammation and the appearance of acne. The aim of this research was to determine whether an ethanol leaf extract emulgel of Jeruju (Achantus ilicifolious) could inhibit Staphylococcus aureus bacteria. The results of the study indicated that at a concentration of 10%, a inhibition zone of 3.8 mm was obtained, at 15% concentration it was 4.7 mm, and at 20% concentration it was 4.8 mm, categorizing the inhibition zones as weak (<5 mm).